Diseño de un sistema de energía fotovoltaica de emergencia para la iluminación en laboratorios - España Salazar, John Alberto (2011)
Photovoltaic solar energy is a clean form of electricity production. The research and the technological development that is done in this thesis makes possible an introduction of this technology in the production of electrical energy in the world to complement the existing sources of conventional energy. Stand-alone photovoltaic systems are a set of interconnected elements to provide power to a given load, the relevant photovoltaic modules are choosing for their performance, because, they are the key to the power generation system works and therefore presents the technology for manufacturing photovoltaic cells in industrial environments. Most solar modules are currently produced from silicon cells. Silicon is the most abundant material on earth, however, required to undergo a refining process by growing a large crystal (monocrystalline or multicrystalline) and then cutting it into this slices which are 0.3 mm thick, this slices are the base material of photovoltaic solar cells. Traditional production of silicon is expensive and highly demanding of energy, in fact, during the cutting process lot of material is wasted, near the 20% in the form of dust. It is also very expensive to recycle this residue, but there are specialized methods to prevent this waste, developed countries continue to investigate ways that minimize the waste of material. However, today's silicon solar cells are dominating the market, accounting for about 90% of the modules that are manufactured in the world. Photovoltaic systems depend on many factors that will determine the best or worst use of solar energy incident or, what is the same, the system performance. For measuring this parameters, a simple way of estimate the number of solar panels needed for the power of 5000 watts required in this project, which involved as the main point average solar radiation of the installation (Pichincha in our case), the voltage level panel and power used, is shown under the criteria detailed technical and economic feasibility for the best option.